(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article provides information on the etiology, pathogenesis, spread, clinical signs, diagnostic methods, recommendations for treatment and prevention of necrobacteriosis, a disease that causes great damage to livestock.